1931
DOI: 10.1017/s0021859600088390
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Yield in the Cereals. Victoria. I. Census studies 1927–29

Abstract: Since the year 1927, observations have been made in Victoria on the development of wheat crops of various varieties grown in four different districts of the State.The method used was based on that employed by Engledow in his “Investigations on Yield in Cereals,” by taking counts on numbers of plants in various “foot length” samples scattered in a systematic manner over the areas studied.The basis of the observations was the determination of the values which comprise yield, viz. p = numbers of plants, e = ears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1932
1932
1956
1956

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Engledow & Kamiah stressed the importance of earliness of tillering and tillering capacity as important indices of yielding ability of wheat varieties growing under highly fertile conditions. Under less favourable conditions in Australia and New Zealand (Forster & Vasey, 1931;Frankel, 1935), ear survival rather than tillering ability is recognized as the important index. Hudson (1934) showed that a high tillering variety would only be expected to have an advantage over a low tillering variety where the amount of food material available was above a certain level.…”
Section: Review Of Previous Literaturementioning
confidence: 99%
“…Engledow & Kamiah stressed the importance of earliness of tillering and tillering capacity as important indices of yielding ability of wheat varieties growing under highly fertile conditions. Under less favourable conditions in Australia and New Zealand (Forster & Vasey, 1931;Frankel, 1935), ear survival rather than tillering ability is recognized as the important index. Hudson (1934) showed that a high tillering variety would only be expected to have an advantage over a low tillering variety where the amount of food material available was above a certain level.…”
Section: Review Of Previous Literaturementioning
confidence: 99%
“…Kiesselbach & Weihing (1933) and Hudson (1941a) attach little importance to plant spacings so long as the optimum seed rate is employed. Spacing experiments conducted in nursery plots by Forster & Vasey (1930), Engeldow (1925) and Frankel (1930) showed that up to a point, wider spacing between plants increased the yield of grain, and that varieties differed greatly in their response to spacing. The disparity in the results between field census and nursery plots was explained by Smith (1937) and Hudson (19416) by a hypothesis of competition between variable plant densities in the field trials, while the competition is uniform in the nursery plots because of even spacing.…”
mentioning
confidence: 99%